1983
DOI: 10.1523/jneurosci.03-01-00069.1983
|View full text |Cite
|
Sign up to set email alerts
|

Transneuronal regulation of tyrosine hydroxylase expression in olfactory bulb of mouse and rat

Abstract: Peripheral afferent input regulates the expression of dopaminergic properties in a population of local circuit intrinsic neurons of the rodent olfactory bulb. Lesions of the olfactory receptor neurons produced in the mouse by intranasal irrigation with either ZnSOl or Triton X-100 and in the rat by surgical deafferentation or axotomy are associated with a decrease in the levels of dopamine (DA), the DA metabolite 3,4-dihydroxyphenylacetic acid (DOPAC), the activity of the enzyme tyrosine hydroxylase (TH), bulb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
201
1
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(230 citation statements)
references
References 4 publications
19
201
1
2
Order By: Relevance
“…1C) at 21 and 28 d after lesion (F (2,17) ϭ 12.95; p Ͻ 0.0001). This finding indicates that olfactory deafferentation lasts at least 1 month and supports previous observations made from distinct methods to induce olfactory deafferentation (Baker et al, 1983;Mandairon et al, 2006;Bastien-Dionne et al, 2010;Parrish-Aungst et al, 2011).…”
Section: Effectiveness Of the Olfactory Lesionsupporting
confidence: 91%
See 1 more Smart Citation
“…1C) at 21 and 28 d after lesion (F (2,17) ϭ 12.95; p Ͻ 0.0001). This finding indicates that olfactory deafferentation lasts at least 1 month and supports previous observations made from distinct methods to induce olfactory deafferentation (Baker et al, 1983;Mandairon et al, 2006;Bastien-Dionne et al, 2010;Parrish-Aungst et al, 2011).…”
Section: Effectiveness Of the Olfactory Lesionsupporting
confidence: 91%
“…1C). TH, the rate-limiting enzyme in the catecholamine synthesis, is expressed only in dopaminergic periglomerular (PG) neurons through an activity-dependent manner (Baker et al, 1983;Kiyokage et al, 2010;Kosaka and Kosaka, 2011). We found a drastic decrease in the TH immunoreactivity in lesioned mice compared with controls ( Fig.…”
Section: Effectiveness Of the Olfactory Lesionmentioning
confidence: 72%
“…It might be surprising that the decrease in A:D synapses is not accompanied by a reduction in TH expression and activity (17,38). TH expression in the glomerular layer is decreased when odorant-induced activity is eliminated with naris occlusion (39) or OSN elimination (40). However, the age-related decrease in glomerular synapses may result in more subtle changes in activity that would be unlikely to affect TH expression.…”
Section: Are Morphological Changes In the Ob Related To Alterations Inmentioning
confidence: 99%
“…This is consistent with regulation of TH protein levels above or below immunohistochemically detectable levels without addition or subtraction of neurons. (3) Many studies have reported activitydependent changes in TH gene and protein expression within cells over a timescale of several hours [17][18][19][20][21][22][23] , and the same has been reported in midbrain 4 .…”
Section: Environmental Manipulationsmentioning
confidence: 78%